Keberlanjutan Wisata Mangrove Silau Laut Dalam Perspektif Ekologi Dan Pariwisata - Nasution, Rahmad Kurnia Abdik; Rachmad Suwardi; I Wayan Sugita; Wayan Darma Sedana; Putu Herny Susanti; Made Budiarsa (Lembaga Pengembangan Kinerja Dosen, 2025)
Silau Laut Mangrove Tourism in Silo Baru Village, Asahan Regency has developed into a community-based ecotourism destination. This study aims to assess the balance between ecological conservation and tourism development at the site. Using qualitative methods, this study employs field observations, stakeholder interviews, and policy analysis. Findings show that although tourism boosts the local economy, significant challenges exist in preserving mangrove ecosystems, particularly from increased tourism activities and oil palm expansion. Strategic recommendations include strict regulations, community empowerment, environmental education, and eco-friendly infrastructure development. Integration of government programs like BRGM reinforces sustainability. The study contributes to developing a sustainable ecotourism management model integrating ecological, social, and economic perspectives.